Oliveira Lima Library. O legado do Don Quixote Gordo - Franco, Gilmara Yoshihara [UNESP]; Da Silva, Márcia Pereira [UNESP] (Universidade Estadual de Maringa, 2013)
Current paper analyzes research sources available in the Oliveira Lima Library, a library in Washington DC, originated from the personal book collection of the Brazilian diplomat Manoel de Oliveira Lima (1867-1928). Sources extant in the library contribute towards the possibility that new researchers would explore through their research work the History of Brazil within a unique stance and which is up to the present a practically unexploited source.
Oliveira Lima Library: The legacy of 'Don Quixote Gordo
Keywords: History of Brazil; Oliveira Lima Library; Research sources